Functional magnetic resonance imaging and functional dyspepsia: Predictive value questioned (International Seven Journal of Multidisciplinary, 2024)
Functional dyspepsia is a challenging condition in gastroenterology, characterized by digestive symptoms without evidence of organic pathology. Conventional diagnostic methods have significant limitations in terms of sensitivity and specificity. This study aims to explore the potential of functional magnetic resonance imaging (fMRI) as an innovative diagnostic approach for functional dyspepsia, with a view to improving diagnostic accuracy and benefiting patients. This integrative literature review, following the PRISMA guidelines, investigated the use of fMRI in the diagnosis of functional dyspepsia. Sixteen articles were selected after rigorous screening, employing detailed descriptive analysis and narrative synthesis. As a result, it was noted that patients with functional dyspepsia exhibit alterations in brain activity, especially in areas associated with sensory processing and emotional control, indicating dysfunction in these regions. It is concluded that fMRI has promising potential in the diagnosis of functional dyspepsia, complementing conventional methods. Although specific pathognomonic patterns have not been identified, the affected brain areas offer a basis for applying fMRI, improving understanding of the condition and enabling more targeted therapies.